(3GdbGehS GdeMjWs - (3GdTjQGRj GdajQhR BHGOj, CHh WGgQ, eLO GdOjf, eMeO Hf jYbhH Hf eMeO Hf EHQGgje Hf YeQ, J (B817 (3g`s
(3ChdgG (B:s
.. (3HGH GdgeRI , aUd GdgeRI (B: (3GdCHGAI, cYHGAI(B: (3GdbUHI, L(B: (3CHGA, gPG ehVY PcQg ceG McGg GHf Lfj Yf SjHhjg, dG GdeYJd ceG Jhgeg GdLhgQj hZjQg hCHCJg HSge(B: (3QejJg Hg CJCI, cMeRI(B: (3GeQCI ef HcQ Hf hGFd(B...s
(3BNQgG (B:s
.. (3GdbTY, HGdaJM(B: (3GdaQh GdNdb, GdbWYI efg(B: (3HgGA, hcfGSI GdMeGe, hjKdK (B... (3L(B: (3bThY, hGdfWY, Ch bWYI ef fWY Ndb, hGdbQHI GdjGHSI, hGdQLd GdefbTY dMeg cHQG, hgj(B: (3HgGA, GdMQHGA, hGdSMGH GdPGgH GdefbTY Yf hLgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B7/146s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GddZIs